CHALLENGE STRESSORS, JOB COMPLEXITY, DAN KREATIVITAS: PERAN MEDIASI WORK ENGAGEMENT DARI PERSPEKTIF JOB DEMAND-RESOURCE MODEL (Jurnal Ekonomi : Journal of Economic, 2022)
This study aims to analyze mediating effect of Work Engagement variable on the effect of Challenge Stressors and Job Complexity toward Creativity. In this study, the method used was quantitative and using questionnaires as a medium to collect data. The sample used in this study is an online transportation driver operating in several cities in Indonesia with a total of 120 samples. The distribution of questionnaires was carried out by means of a survey via Google Form which would be distributed via social media and distributed directly to the respondents. The data that has been obtained for this study were then analyzed using linear regression analysis and tested with the SPSS 25 version program and using Sobel Test Statistics to test the mediation effect. Results have shown that Challenge Stressors has a positive and significant effect on Work Engagement, Job Complexity has no positive and significant effect on Work Engagement, Work Engagement has a positive and significant effect on Creativity, and Challenge Stressor and Job Complexity both have a positive and significant effect on Creativity. Then, Work Engagement is proven to mediate the effect of Challenge Stressors on Creativity, while Work Engagement is not proven to mediate the effect of Job Complexity on Creativity.